2013
DOI: 10.1038/pr.2013.242
|View full text |Cite
|
Sign up to set email alerts
|

Definition and quantification of acute inflammatory white matter injury in the immature brain by MRI/MRS at high magnetic field

Abstract: Background: Lipopolysaccharide (LPS) injection in the corpus callosum (CC) of rat pups results in diffuse white matter injury similar to the main neuropathology of preterm infants. The aim of this study was to characterize the structural and metabolic markers of acute inflammatory injury by high-field magnetic resonance imaging (MRI) magnetic resonance spectroscopy (MRS) in vivo. Methods: Twenty-four hours after a 1-mg/kg injection of LPS in postnatal day 3 rat pups, diffusion tensor imaging and proton nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 43 publications
6
34
0
Order By: Relevance
“…A total of 15 Sprague-Dawley pups coming from two litters (7.96 ± 0.45 g weight, Charles River, Senneville, Qc, Canada) were randomized in two different groups: LPS ( n = 6) which were injected at postnatal day 3 (P3, equivalent to human gestational age of about 24–28 weeks (Sizonenko et al, 2003; Lodygensky et al, 2014) with a solution of lipopolysaccharide diluted in saline (1 mg/kg in 0.5 μL, E. Coli , serotype 055:B5, Sigma St Louis, MO) and a sham control group NaCl ( n = 9), injected with saline alone. Injection site was the left corpus callosum at a level equivalent to P-7, c9 (Lodygensky et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 15 Sprague-Dawley pups coming from two litters (7.96 ± 0.45 g weight, Charles River, Senneville, Qc, Canada) were randomized in two different groups: LPS ( n = 6) which were injected at postnatal day 3 (P3, equivalent to human gestational age of about 24–28 weeks (Sizonenko et al, 2003; Lodygensky et al, 2014) with a solution of lipopolysaccharide diluted in saline (1 mg/kg in 0.5 μL, E. Coli , serotype 055:B5, Sigma St Louis, MO) and a sham control group NaCl ( n = 9), injected with saline alone. Injection site was the left corpus callosum at a level equivalent to P-7, c9 (Lodygensky et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Injection site was the left corpus callosum at a level equivalent to P-7, c9 (Lodygensky et al, 2014). All injections were performed with an ultrasound-guided micro injector (Micro4 from World Precision Instruments) at a rate of 0.1 μL/min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To mimic infection/inflammatory developmental injury, bacterial Lipopolysaccharide (LPS) challenge is widely use (Edwards, 2006; Dean, 2011; Hagberg, 2002). We have induced brain injury in the P3 rat pup with intracerebral LPS injection and showed that the typical injury is reduced by dam Lf supplementation from birth and during lactation (Ginet et al 2016): at P25 ventricular dilatation that is seen on MRI and histopathology after this inflammatory injury (Lodygensky et al 2014) was reduced in the injured pups receiving LF through lactation. At weaning (P25) central white matter fibres of the striatum are altered with increased size of the diameter of the axons, that appears to be partially reversed by Lf supplementation.…”
Section: Lactoferrin In Brain Development and Injurymentioning
confidence: 99%
“…On the metabolic level, using proton magnetic spectroscopy ( 1 H-MRS) at ultra-high magnetic field, intracerebral LPS injection in P3 rat induced acute (24h post-injection) specific changes in the “neurochemical profile” of central white matter (corpus callosum) (Lodygensky et al 2014). LPS-induced alterations (increase or decrease) in brain metabolites concentration also occurred in other central white matter fibres (striatum) after LPS injection and Lf supplementation reduced these acute changes.…”
Section: Lactoferrin In Brain Development and Injurymentioning
confidence: 99%